ANALISIS KEBUTUHAN DALAM PERENCANAAN PENDIDIKAN ISLAM UNTUK MENINGKATKAN MUTU DAN RELEVANSI PEMBELAJARAN: SEBUAH KAJIAN LITERATUR - Wardhani, Suryaningtiyas Puspa; Nurjanah, Siti; Hidayat, Rahmad; lestari, Tri yuli; Junnaidah; Abdurrahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the needs in Islamic education planning to enhance the quality and relevance of learning in the modern era. Using a literature review method, this research identifies three primary needs: curriculum relevance, innovative teaching methods, and teacher competency improvement. The analysis reveals that the Islamic education curriculum must adapt to societal and technological developments without compromising Islamic values. Additionally, interactive technology-based learning methods can increase student engagement, while teacher competencies in technology and innovative teaching are crucial for the success of Islamic education. The findings of this study emphasize the importance of an integrated approach combining these three aspects to achieve adaptive, relevant, and high-quality Islamic education. This research is expected to contribute to the formulation of Islamic education policies that better meet contemporary demands.